CD11b+ and Sca-1+ Cells Exert the Main Beneficial Effects of Systemically Administered Bone Marrow-Derived Mononuclear Cells in a Murine Model of Mixed Th2/Th17 Allergic Airway Inflammation - Cruz, Fernanda F. (Stem Cells Transl Med, 2016)
Systemic administration of bone marrow-derived mononuclear cells (BMDMCs) or bone marrow-derived mesenchymal stromal cells (MSCs) reduces inflammation and airway hyperresponsiveness (AHR) in a murine model of Th2-mediated eosinophilic allergic airway inflammation. However, since BMDMCs are a heterogeneous population that includes MSCs, it is unclear whether the MSCs alone are responsible for the BMDMC effects. To determine which BMDMC population(s) is responsible for ameliorating AHR and lung inflammation in a model of mixed Th2-eosinophilic and Th17-neutrophilic allergic airway inflammation, reminiscent of severe clinical asthma, BMDMCs obtained from normal C57Bl/6 mice were serially depleted of CD45, CD34, CD11b, CD3, CD19, CD31, or Sca-1 positive cells. The different resulting cell populations were then assessed for ability to reduce lung inflammation and AHR in mixed Th2/Th17 allergic airway inflammation induced by mucosal sensitization to and challenge with Aspergillus hyphal extract (AHE) in syngeneic C56Bl/6 mice. BMDMCs depleted of either CD11b-positive (CD11b+) or Sca-1-positive (Sca-1+) cells were unable to ameliorate AHR or lung inflammation in this model. Depletion of the other cell types did not diminish the ameliorating effects of BMDMC administration. In conclusion, in the current model of allergic inflammation, CD11b+ cells (monocytes, macrophages, dendritic cells) and Sca-1+ cells (MSCs) are responsible for the beneficial effects of BMDMCs. SIGNIFICANCE: This study shows that bone marrow-derived mononuclear cells (BMDMCs) are as effective as bone marrow-derived mesenchymal stromal cells (MSCs) in ameliorating experimental asthma. It also demonstrates that not only MSCs present in the pool of BMDMCs are responsible for BMDMCs’ beneficial effects but also monocytes, which are the most important cell population to trigger these effects. All of this is in the setting of a clinically relevant model of severe allergic airways inflammation and thus provides further support for potential clinical use of cell therapy using MSCs, BMDMCs, and also adult cells such as monocytes in patients with severe asthma.